(untitled) (The Review of Diabetic Studies, 2025)
Community paramedicine has emerged as a transformative extension of prehospital care, offering proactive, preventive, and community-centered services that strengthen emergency preparedness in daily life. This systematic integrative review examines the influence of community paramedicine–led interventions on public readiness, safety behaviors, and community resilience. Following PRISMA guidelines, peer-reviewed studies from 2010–2025 were analyzed to evaluate how paramedics contribute to risk awareness, preparedness education, early hazard recognition, and community-based response capabilities. Evidence shows that paramedic-led programs—such as home-safety assessments, chronic disease monitoring, public first-aid training, community risk mapping, and disaster-preparedness education—significantly enhance individual and collective readiness. Interventions also foster behavioral change related to CPR performance, bleeding control, evacuation decision-making, and hazard prevention in households and workplaces. Additionally, community paramedicine strengthens system resilience by expanding health access, reducing emergency burden, and improving communication between healthcare and public safety structures. The findings highlight the paramedic’s evolving role as an educator, risk communicator, and frontline resilience-builder extending beyond emergency response. Practical recommendations are provided for policymakers seeking to strengthen national preparedness strategies.